Potential of fermented herbal extracts to modulate digestion and gut microbiota during the weaner and fattening period on commercial pig farms - Metzler-Zebeli, Barbara U.; Nöllenburg, Natalia; Koger, Simone; Schobersberger, Katharina; Vötterl, Julia C.; Leeb, Christine (Frontiers in Veterinary Science, 2025)
Due to varying farm environments, the effect of feed additives on the gut microbiota and function in pigs may differ among farms. The present study aimed to evaluate the effect of a fermented herbal extract (FHE) on feed digestibility, fecal microbiota composition, and microbial metabolites under commercial production conditions on three pig farms throughout the weaner and fattening period. A total of 760 pigs across three farms were randomly allocated to one of two diets (control or 1% FHE) after weaning. On each farm, feces were collected from the same three barrows and three gilts per treatment at the weaner, mid, and the end of fattening period for microbiota, short-chain fatty acid (SCFA), and digestibility analyses. Total DNA from feces was extracted for 16S rRNA amplicon sequencing. Results were specific for farm, production stage (age), and sex. The FHE did not markedly affect the apparent total tract digestibility (ATTD) on Farms A and C (p > 0.05). On Farm B, the FHE improved the ATTD of crude ash by 11.4% in the mid-fattening period compared to the control (p < 0.05). On Farm B, the FHE increased (p = 0.041) the SCFA concentrations in feces of barrows (but not in gilts) compared to the control, but only in the mid-fattening period. On Farm C, FHE effects on SCFA fluctuated with age but were different compared to Farm B. The FHE increased (p < 0.05) or tended to increase (p < 0.10) species richness (observed features, Farms A and C) and diversity (Shannon, only Farm A) compared to the control in the weaner period. Likewise, more FHE-related changes in bacterial abundances were found in the weaner compared to the mid and end of fattening periods across farms, indicating that the FHE has more gut microbiota-modulating capabilities in younger pigs. The FHE-related changes in the bacterial composition were farm-specific and probably linked to the available fermentable substrate in the hindgut. Overall, results demonstrate the importance of investigating feed supplements like FHE on several farms and different production conditions to disentangle their gut physiological and microbial effects in weaner and fattening pigs.